Toward a Smart City Pontianak: A Study of Digital Governance Effectiveness as a Moderator of the Relationship Between Work Culture, HR Management, and Public Satisfaction - Sulaiman, Sulaiman; Trimawarni, Andjani; Wahyuni, Endang; Listiana, Yunika Depri (Universitas Pattimura, 2025)
This study examines the impact of implementing a digital government system as a strengthening factor in the relationship between organizational work culture and human resource management on public satisfaction levels in Pontianak City. The research aims to understand the effectiveness of digital governance in supporting government organizational performance to achieve a more optimal smart city concept. The research method used is quantitative research with an explanatory survey approach, involving 378 respondents selected through a proportional stratified random sampling method. Data collection was conducted using a structured questionnaire, and data analysis was carried out using Structural Equation Modeling (SEM) techniques processed with the SmartPLS version 4.0 application. The study results show that the successful implementation of a digital government system significantly strengthens the influence of work culture on public satisfaction levels. The findings also indicate that the synergy between digital government systems, organizational work culture, and human resource management can increase the public satisfaction index by up to 42.3% compared to traditional methods. This research contributes to the development of social humanities sciences, particularly in understanding the role of digital governance as a reinforcement in the relationship between human resource management and public satisfaction in urban contexts moving towards smart cities.